RApi m 3 and rApi m 10 improve detection of honey bee sensitization in Hymenoptera venom‐allergic patients with double sensitization to honey bee and yellow jacket venom. Issue 12 (8th September 2015) - Frick, M.; Müller, S.; Bantleon, F.; Huss‐Marp, J.; Lidholm, J.; Spillner, E.; Jakob, T.
Abstract: Recombinant allergens improve the diagnostic precision in Hymenoptera venom allergy (HVA), in particular in patients with double sensitization to both honey bee (HBV) and yellow jacket venom (YJV). While currently available vespid allergens allow the detection of >95% of YJV‐allergic patients, the sensitization frequency to the only available HBV marker allergen rApi m 1 in HBV‐allergic patients is lower. Here, we demonstrate that sIgE to additional HBV marker allergens rApi m 3 and rApi m 10 allows the detection of genuine HBV sensitization in 46–65% of Api m 1 negative sera. This is of particular relevance in patients with double sensitization to HBV and YJV that did not identify the culprit insect. Addition of sIgE to rApi m 3 and rApi m 10 provides evidence of HBV sensitization in a large proportion of rApi m 1‐negative patients and thus provides a diagnostic marker and rationale for VIT treatment with HBV, which otherwise would have been missing.